A Study on The Validity and Reliability of The Personality Belief Questionnaire-Short Form in Turkish Community Sample - Yusuf BILGE; Yildiz BILGE (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: This study aims to test psychometric properties of The Personality Belief Questionnaire-Short Turkish Form (PBQ-STF) in the community sample and to determine the validity and reliability of the Borderline Personality Disorder subscale, which was not included in the previous Turkish adaptation studies. Method: PBQ-STF was administered to a sample of 650 participants (in the age range of 18-66 years, 362 women (55.7%) and 288 men (44.3%)). Test-retest reliability was applied on a group of 30 person from sample with interval four weeks. For testing convergent validity, Beck Depression Inventory (n=108), State-Trait Anxiety Inventory (n=100) and Dysfunctional Attitude Scale (n=108) were also employed. Results: Cronbachs alpha values varied between .70-.84. Test-retest reliabilities were .77-.90. PBQ-SFs all subscales were correlated each other positively. In the exploratory factor analysis (EFA), PBQ-STF subscales revealed two factors explained 70,89% of the total variance. In the confirmatory factor analysis (CFA), it was seen adaptive statistical values of scale were at acceptable/agreeable level. Conclusion: According to the results obtained from the analyzes made, it was determined that PBQ-STF has strong psychometric evidence and is a reliable and valid scale that can be used in evaluating personality beliefs. [JCBPR 2019; 8(1.000): 7-15]